Impact of Patin Fish Flour on Mocaf Semprit Cookies - Wahyuningsih, Wahyuningsih; Sukma, Shella Ovita; Wibowotomo, Budi (Jurusan Pendidikan Kesejahteraan Keluarga, Fakultas Teknik, Universitas Negeri Semarang, 2024)
This study aims to determine the differences in preference, protein content, and water content in Mocaf flour Semprit cookies with the addition of Patin fish flour, evaluated based on taste, color, texture, and aroma. Mocaf flour and Patin fish flour are expected to produce high-protein, locally sourced Semprit cookies as a healthy snack. The objects of this study were Mocaf flour Semprit cookies with the addition of Patin fish flour at 0%, 10%, 15%, and 20%. The experimental design used was completely randomized. The independent variable in this study is the addition of Patin fish flour at 0%, 10%, 15%, and 20%, a count of the total Mocaf flour used in making Semprit cookies. The dependent variables are the differences in preference, protein, and water content of the experimental Semprit cookies. The experimental design used was completely randomized. Data collection methods included preference testing and testing for protein and water content. The data analysis methods used were the Kruskal-Wallis and Mann-Whitney tests. Protein content was tested using the Kjeldahl method, and water content was tested using the gravimetric method. The results showed differences in color, texture, aroma, and taste preference indicators. Protein content test results for the 0% formula were 8.79%, 10%: 9.06%, 15%: 10.41%, and 20%: 12.3%. Water content was 5.58% for 0%, 5.9% for 10%, 6.34% for 15%, and 6.61% for 20%.